Arqueología de las sociedades locales en la Alta Edad Media : San Julián de Aistra y las residencias de las élites rurales - Quirós Castillo, Juan Antonio; Reynolds, Andrew (Historical archaeologies series., 2023)
This volume brings together a large number of specialized studies and provides an interpretation of the site of San Julián de Aistra (Zalduondo-Araia, Alava) in terms of socio-political practices that define the main characteristics of early medieval local societies in the northwest of the Iberian Peninsula.